2020
DOI: 10.1002/essoar.10503543.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unprecedented reduction in airborne aerosol particles and nitrogen dioxide level in response to COVID-19 pandemic lockdown over the Indo-Pak region

Abstract: The present study have used space observations of NO emission (OMI) and aerosol optical depth (AOD) (MODIS) from the last couple of years (2015)(2016)(2017)(2018)(2019) to investigate the changes in air pollution in response to COVID-19 pandemic during the lockdown period (Mar-May, 2020) over the Indo-Pak region. Result of this study reveals a huge drop in air pollution that accounted for 40-50% reduction in NO emissions and 45% in AOD over the whole Indo-Pak region. The major metropolitan areas (cities) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It has been discovered that the running mean of NO 2 value during January-March 2020 (BL) has a fluctuation trend that differs from the average time series of 2016 to 2019. During the SL period (April-June 2020), the time series of average NO 2 emissions over all three cities in Pakistan moves with a slight fluctuation when compared to the baseline period (2016-2019) [28]. It has been observed that for the cities of Lahore and Islamabad, the anomaly changes in NO 2 emissions from January to March 2020 (before the lockdown) show a positive trend, demonstrating the high emissions from industrial sources and transportation compared to previous years.…”
Section: (D) City Level Analysismentioning
confidence: 99%
“…It has been discovered that the running mean of NO 2 value during January-March 2020 (BL) has a fluctuation trend that differs from the average time series of 2016 to 2019. During the SL period (April-June 2020), the time series of average NO 2 emissions over all three cities in Pakistan moves with a slight fluctuation when compared to the baseline period (2016-2019) [28]. It has been observed that for the cities of Lahore and Islamabad, the anomaly changes in NO 2 emissions from January to March 2020 (before the lockdown) show a positive trend, demonstrating the high emissions from industrial sources and transportation compared to previous years.…”
Section: (D) City Level Analysismentioning
confidence: 99%
“…The study reported a 14% reduction in PM2.5 and 30% reduction in NO2, a 25% reduction in CO and a 3% rise in O3 during the lockdown phase. Arshad et al (2020) attempted AOD and NO2 variations during COVID-19 lockdown phase using satellite datasets over major cities of India and Pakistan. The study reported a reduction of 32-42% in NO2 and ~45% reduction in AOD over the entire Indo-Pak region.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than a strict lock-down, Pakistan implemented "smart lockdown" to cause minimal adverse impact on social and economic conditions while reducing the spread of infection successfully. New satellite imageries released by ESA and recently published studies also reported that the average tropospheric NO 2 over the Asian counties reduced 40 À 50% in 2020 during the quarantine period compared to the average of last year (Arshad et al 2020). The recent decline in tropospheric NO 2 is associated with less consumption of fossil fuels (Sharma et al 2020;Wang et al 2021) due to the sharp reduction in transport and industry, which ultimately resulted in less air pollution (Mahato et al 2020).…”
Section: Regional Changes In Tropospheric Nomentioning
confidence: 94%